Performances Development of Traditional Settlement in Skonjing Village, Ogan Ilir, South Sumatra - L. Prima; F. Amalia; A. Arief; Q. A Harjuniertha; M.R. Agil; A.R Ali (Archvisual: Jurnal Arsitektur dan Perencanaan, 2024)
The traditional settlement in Skonjing Village has unique characteristics that reflect the local community's close relationship with the natural surroundings. Using natural materials, especially wood, in house construction reflects the sustainable and eco-friendly principles the locals have implemented. The buildings built in the early period in Skonjing Village were mostly stilt houses that used materials easily found around the location. Through observation of field surveys and interviews with residents, this research identified the characteristics of Skonjing Village's traditional settlement based on their function, use of materials, and visual appearance that have been changed and threaten to be dismissed. It was discovered that the development performances of Skonjing Village started from the outskirts of the Ogan tributary and spread outwards, away from the riverbank. Understanding the characteristics of these traditional houses is crucial for preserving the cultural identity of Skonjing Village.